KONSTRUKSI SOSIAL PEMBAGIAN KERJA DAN PENGUPAHAN BURUH TANI - Eko Setiawan (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2017)
Abstract: Wage is still one of the issues that has always been in thespotlight, especially in developing countries such as Indonesia, especially inthe agricultural sector. Women in the work environment in the public sectorare often still distinguished from men in terms of the division of labor. Thedifference in the division of labor between men and women in agriculture,this is what affects the wage system and the tendency of gender inequalityand injustice. This is given that wage are a major component of one’sincome, so the wage rate is one indicator that can reflect the welfare of thecommunity. One of the solutions that must be done is the need for criticalassessment of the livelihood of the workers which has been a problem,especially the fulfillment of the wage of women laborers who are still low. Abstrak: Upah masih menjadi permasalahan terutama di negara-negaraberkembang, khususnya disektor pertanian. Dalam pembagian kerjadi sektor publik, perempuan dan laki-laki masih dibedakan. Perbedaanpembagian kerja antara laki-laki dan perempuan inilah yang kemudianmempengaruhi sistem pengupahan, yang pada akhirnya melahirkanketimpangan dan ketidakadilan gender.Hal ini mengingat bahwa upahmerupakan komponen utama dari pendapatan seseorang. Upah merupakansalah satu indikator yang dapat mencerminkan kesejahteraan masyarakat. Salah satusolusi yang harus dilakukan adalah perlunya kajian kritis atas penghidupan buruh yang selama ini masih menjadi persoalan,khususnya upah buruh perempuan tani yang masih rendah.